Possible Involvement of Mitochondrial Energy-Producing Ability in the Development of Right Ventricular Failure in Monocrotaline-Induced Pulmonary Hypertensive Rats - Takuya Daicho; Tatsuya Yagi; Yohei Abe; Meiko Ohara; Tetsuro Marunouchi; Satoshi Takeo; Kouichi Tanonaka (Elsevier, 2009)
The present study was undertaken to explore the possible involvement of alterations in the mitochondrial energy-producing ability in the development of the right ventricular failure in monocrotaline-administered rats. The rats at the 6th week after subcutaneous injection of 60 mg/kg monocrotaline revealed marked myocardial hypertrophy and fibrosis, that is, severe cardiac remodeling. The time-course study on the cardiac hemodynamics of the monocrotaline-administered rat by the cannula and echocardiographic methods showed a reduction in cardiac double product, a decrease in cardiac output index, and an increase in the right ventricular Tei index, suggesting that the right ventricular failure was induced at the 6th week after monocrotaline administration in rats. The mitochondrial oxygen consumption rate of the right ventricular muscle isolated from the monocrotaline-administered animal was decreased, which was associated with a reduction in myocardial high-energy phosphates. Furthermore, the decrease in mitochondrial oxygen consumption rate was inversely related to the increase in the right ventricular Tei index of the monocrotaline-administered rats. These results suggest that impairment of the mitochondrial energy-producing ability is involved in the development of the right ventricular failure in monocrotaline-induced pulmonary hypertensive rats. Keywords:: monocrotaline, right ventricular hypertrophy, right ventricular failure, mitochondrial dysfunction, high-energy phosphate